Gravimetric Investigations in the Region of the Soviet Antarctic Stations Lazarev and Novolazarevskaya (Gravimetricheskie Issledovanie v Rayone Sovetskikh Antarkticheskikh Stansii Lazarev i Novolazarevskaya) - Kogan,A. L.; Stroev,P. A. (1974)
A description of all the gravimetric investigations in the region of Princess Astrid Coast is presented. These are land and marine surveys carried out from 1959 to 1964. These works were continued in 1969 by the XIV Soviet Antarctic Expedition. On the continental glacier, within the general complex of geophysical investigations, gravity measurements were carried out at 41 points. A catalog of these points is presented. (Author) Technical trans. of Moscow Univ. Gosudarstvennyi Astronomicheskii Institut. Trudy (USSR) v43 n2 p3-7 1972, by George Synenko.